Loss of Paip1 causes translation reduction and induces apoptotic cell death through ISR activation and Xrp1 - Xue, Maoguang; Cong, Fei; Zheng, Wanling; Xu, Ruoqing; Liu, Xiaoyu; Bao, Hongcun; Sung, Ying Ying; Xi, Yongmei; He, Feng; Ma, Jun; Yang, Xiaohang; Ge, Wanzhong (Cell death discovery, 2023)
Regulation of protein translation initiation is tightly associated with cell growth and survival. Here, we identify Paip1 , the Drosophila homolog of the translation initiation factor PAIP1 , and analyze its role during development. Through genetic analysis, we find that loss of Paip1 causes reduced protein translation and pupal lethality. Furthermore, tissue specific knockdown of Paip1 results in apoptotic cell death in the wing imaginal disc. Paip1 depletion leads to increased proteotoxic stress and activation of the integrated stress response (ISR) pathway. Mechanistically, we show that loss of Paip1 promotes phosphorylation of eIF2α via the kinase PERK, leading to apoptotic cell death. Moreover, Paip1 depletion upregulates the transcription factor gene Xrp1 , which contributes to apoptotic cell death and eIF2α phosphorylation. We further show that loss of Paip1 leads to an increase in Xrp1 translation mediated by its 5’UTR. These findings uncover a novel mechanism that links translation impairment to tissue homeostasis and establish a role of ISR activation and Xrp1 in promoting cell death.